Early Life Domestic Pet Ownership, and the Risk of Pet Sensitization and Atopic Dermatitis in Preschool Children: A Prospective Birth Cohort in Shanghai - Li, Chunxiao; Chen, Qian; Zhang, Xi; Li, Huaguo; Liu, Quanhua; Fei, Ping; Huang, Lisu; Yao, Zhirong (Frontiers in Pediatrics, 2020)
Background: Although domestic pet ownership is on the rise, the impact of early life pet ownership on children’s pet sensitization and atopic dermatitis (AD) remains controversial. Methods: Shanghai Allergy Cohort is an ongoing prospective study followed up to the age of 5 years. Pregnant mothers were recruited, and their offspring were followed up every year by a group of pediatricians. Information on furred pet ownership was collected by the questionnaire. AD was diagnosed by dermatologists according to disease history and Williams criteria at 5 years ± 1 months. Skin prick test (SPT) was performed to determine sensitization to specific allergens. Multiple logistic regression models were used to evaluate the associations between pet ownership and AD, dog/cat sensitization. Results: In the 538 children at preschool age, 112 (20.82%) were diagnosed with AD. Dermatophagoides pteronyssinus and Dermatophagoides farina were the most common allergens, and almost ten percent of children were positive to dog and cat. The percentage of positive SPT reactors at 5-year old was 65.28% in the group of children with AD, higher than that in non-AD group (44.57%). Domestic pet ownership at both infant and preschool period was positively associated with an increased risk of sensitization to dog (OR adjusted=2.85 [95% CI: 1.08-7.50 for infant exposure], OR adjusted=2.73 [95% CI: 1.33-5.61] for preschool exposure), and interestingly, pet ownership at infant period negatively associated with higher risk of AD at 5-year old (OR adjusted=0.33 [95% CI: 0.12-0.88]). Conclusion: This is the first prospective birth cohort study in Shanghai that found half of preschool children had positive allergen sensitization even in the non-AD children. Although early life exposure to dog may increase the risk of dog sensitization, it significantly decreased the risk of AD. The underlying mechanisms warrant further investigation.